The intergenerational consequences of war: anxiety, depression, suicidality, and mental health among the children of war veterans. (24th March 2018) - Forrest, Walter; Edwards, Ben; Daraganova, Galina
Abstract: Background: The long-term effects of military deployment on the mental health of war veterans have been investigated extensively, but few studies have examined the long-term impact of parental deployment on children's mental health. Methods: Using a retrospective, multigenerational survey and propensity score analysis to adjust for selection effects and endogeneity bias, we investigated the impact of parental deployment on the mental health of the adult children of Australian veterans of the Vietnam War. We analysed data from 1966 adult men (35%) and women (65%) whose fathers ( N  = 1418) were selected at random from the population of surviving men who served in the Australian army during the Vietnam War (1962–75). Mean age of respondents was 37. The main outcome measures were self-reported diagnosis or treatment for anxiety and depression (i.e. lifetime and previous 12 months), suicidality based on Psychiatric Symptom Frequency Scale, and current mental health as measured by the Mental Health Inventory of the SF-36. The key independent variable was whether their fathers were deployed to the Vietnam War. Results: Almost 40 years after the war, the adult children of deployed veterans were more likely to have been diagnosed with anxiety [odds ratio (OR) = 1.54, confidence interval (CI) = 1.04, 2.28] and depression (OR = 1.77, CI = 1.03, 3.05), to have had thoughts of suicide and self-harm (OR = 2.39, CI = 1.57, 3.65) and to have made suicidal plans (OR = 3.52, CI = 1.40, 8.85) than the offspring of comparable, non-deployed army veterans. They also reported poorer current mental health (Coefficient = −5.08, CI = −6.60 – −3.56). Conclusions: The results imply that there are significant and enduring adverse effects of parental deployment on the mental health of children in military families, and provide some insight into the potential long-term impacts of recent military engagements in Afghanistan and Iraq.